2012
DOI: 10.1002/app.36245
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of novel organosilicon‐modified polyurethane

Abstract: Organosilicon-modified polyurethane have been synthesized using the prepolymer method and characterized by Fourier infrared (FTIR) spectroscopy, wide angle X-ray diffraction (WAXD), scanning electron microscopy (SEM), thermogravimetric analysis (TGA), differential thermal analysis (DTA), solvent resistance analysis, and stress-strain tests. The FTIR spectra show that the polyurethane is fully reacted and polydimethylsiloxane (PDMS) is chemically incorporated into the copolymer. SEM reveals a multiphase structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…DTA experiments agree well with the TGA thermograms. There were two exothermic peaks at about 400 and 480 °C, likely associated with the decomposition process of hard segments (i.e., isocyanate + chain extender) and soft segments (i.e., polyol) …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DTA experiments agree well with the TGA thermograms. There were two exothermic peaks at about 400 and 480 °C, likely associated with the decomposition process of hard segments (i.e., isocyanate + chain extender) and soft segments (i.e., polyol) …”
Section: Results and Discussionmentioning
confidence: 99%
“…There were two exothermic peaks at about 400 and 480 °C, likely associated with the decomposition process of hard segments (i.e., isocyanate + chain extender) and soft segments (i.e., polyol). 33 Porosity and Degree of Cross-Linking. Coating porosity measurements showed that E44 had a great influence on porosity (Figure 8).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…53,55,56 The absorption band around 3320 cm À1 indicated the N-H group in urethane. 57,58 The peaks at 2940 and 2854 cm À1 were asymmetric and symmetric vibrations of the -CH 2 group. 59 The peaks at 1530 and 1220 cm À1 were assigned to amide (-C-N-) in urethane (-NHCOO-).…”
Section: Results and Discussion Ftir Resultsmentioning
confidence: 99%
“…The surface SEM images of PUA and SPUA films are shown in Figure 3 . The PUA ( Figure 2 a) film shows a typical microphase separation morphology, in which many protrusions of hard-segment domains have dispersed in the soft segments [ 44 ]. Incorporation of only 5 wt % MI or MII into PUA could significantly decrease the microphase separation ( Figure 3 B,F), evidenced by the fact that only a little bit of agglomerations could be observed (inset).…”
Section: Resultsmentioning
confidence: 99%